(untitled) (TUTA Journal, 2024)
The argument to prepare this research paper is that to analyze the various aspects of electoral systems which are practiced in the different countries of the world and discuss the better electoral system in Nepal as it is preparing itself for the system of federalism. It also studies the inclusive democracy and the electoral system practiced in the contemporary politics and the CA polls. The issue of election at different levels in federal system, in which inclusive democracy is again the question of national debate. It tries to raise the issue of the election system to be adopted in the upcoming elections. As Nepal faced the challenging situation in contemporary politics and the model of FPTP and List PR system practiced in the CA elections in 2008 and 2013. Here is the description of electoral system practiced in the world and their merits, demerits which give the clear idea to judge the electoral system suitable for a country like Nepal. The paper analyses the CA election 2008 and its result. Even it discusses about the reforms needed for the FPTP and List PR, Parallel mixed system or any other electoral system which can be more proportional and inclusive in the context of Nepal.